Research on New Regional Creation Business Model Utilizing Social Network and Crowdfunding - Takefumi Matsuda (Bright Institute, 2022)
The development of IT has made it possible to create a bridge between regional and urban residents using things like SNS and crowd funding. The decline of local communities due to a reduced population is an important factor that has an impact on the future of the entirety of Japan. In response to this problem, the young generation is making attempts to vitalize regions based on a relationship of sharing, co-creation, and sympathy that come from sharing the same space by using IT. The general idea of a share village is that old Japanese-style homes in regions are regarded as villages and multiple hometown areas can be chosen for SATOGAERI (Country life experience). This project is an initiative with the objective of preserving old Japanese-style homes that are pieces of history and saving Japan's original landscape for the next 100 years. Thus, bridges are built between regional residents and the resources of urban residents based on a perspective of generating social capital and focusing on structures that are maintained by many people. This paper examines the possibility of generating new social capital through regional vitalization and reviving local communities by creating such bridges, and it presents a new design for local communities.